Dlaczego działania transgresyjne intrygują i inspirują do badań (także) autobiograficznych? - Okraj, Zofia (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
Transgressions as creative, innovative, expansive activities that involve going „beyond” the existing knowledge, skills, and attainment of human beings are an affirmation of human ability for continuous development, and thus involve crossing different barriers and transcending following borders. The issue of transgression and its various aspects – from the motives of taking such actions through their mechanisms and effects, inspires scientists both for theoretical considerations and for empirical research, especially in the qualitative realm, where autobiographical research can play a special role in transgression, giving transgressors the possibility of narrative transmission. And researchers have the opportunity to gain knowledge: why?, how, and what effect? – as they were undertaking transgressive activities. The purpose of the study is to make a brief outline of the nature, types and motives of transgression, and to look for sources of research, inspiration for this phenomenon, taking into account both the difficulties and the possibilities of their exploration in the field of qualitative research, mainly of autobiographical kind.